Impact of Gender Equality Policies on Women’s Career Mental Health and Well-Being - R. V. Abraham; T. Q. Rowley (Studies in Social Science & Humanities, 2024)
This paper examines the impact of gender equality policies on women’s career mental health and well-being in Canada. Over the past few decades, Canada has implemented a variety of legislative measures aimed at promoting gender equality, including pay equity, parental leave, and anti-discrimination laws. These policies have been instrumental in creating more inclusive and supportive workplace environments, improving job satisfaction, and enhancing overall mental health for women. However, despite significant progress, challenges such as persistent wage gaps, underrepresentation in leadership roles, and workplace harassment continue to hinder the full realization of gender equality. Using a qualitative research approach, this study explores the experiences of women across different industries and backgrounds to understand how these policies impact their mental health and career progression. The findings highlight the importance of strengthening policy implementation, promoting cultural change within organizations, and addressing intersectional inequalities to further improve the mental health and well-being of women in the workforce. Recommendations for policymakers and organizations are provided to enhance the effectiveness of gender equality policies and create more equitable workplaces.